Pengembangan Media Pembelajaran Articulate Story Line 3 Berbasis Project Based Learning pada Materi Seni Rupa Bereksperimen di Kelas IV Sekolah Dasar - Aini, Raysah Qurrata; Yunisrul, Yunisrul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop valid, practical, and effective Articulate Storyline 3 learning media based on Project Based Learning for the Fine Arts subject “Experimenting with Textures” in fourth grade elementary school. This study is a development study using the ADDIE model (analysis, design, development, implementation, evaluation). Data were collected using validation and practicality instruments, then analyzed using validity and practicality analysis techniques. The results showed that the developed media obtained a validation score of 96% from subject matter experts, 92% from language experts, and 90% from media experts, with an average of 93% (highly valid). The practicality test also showed excellent results. At SDIT Alam Talago, the response rate from teachers reached 94% and from students 94.69%. At SDN 19 Santur, the response rate from teachers was 97% and from students 95.33%. These findings indicate that media is practical for use in learning. The effectiveness of media is demonstrated by the improvement in student learning outcomes. The average pretest score at the pilot school was 57.14%, which increased to 90.71% on the posttest. Thus, Articulate Storyline 3 learning media based on Project Based Learning has been proven to be valid, practical, and effective in improving student learning outcomes in Fine Arts in fourth grade elementary school.